Mining the role of angiopoietin‐like protein family in gastric cancer and seeking potential therapeutic targets by integrative bioinformatics analysis. (14th May 2020) - Tang, Cheng; Chen, Erbao; Peng, Ke; Wang, Haiwei; Cheng, Xi; Wang, Yan; Yu, Shan; Yu, Yiyi; Cui, Yuehong; Liu, Tianshu
Abstract: Background: The indistinctive effects of antiangiogenesis agents in gastric cancer (GC) can be attributed to multifaceted gene dysregulation associated with angiogenesis. Angiopoietin‐like (ANGPTL) proteins are secreted proteins regulating angiogenesis. They are also involved in inflammation and metabolism. Emerging evidences have revealed their various roles in carcinogenesis and metastasis development. However, the mRNA expression profiles, prognostic values, and biological functions of ANGPTL proteins in GC are still elucidated. Methods: We compared the transcriptional expression levels of ANGPTL proteins between GC and normal gastric tissues using ONCOMINE and TCGA‐STAD. The prognostic values were evaluated by LinkedOmics and Kaplan–Meier Plotter, while the association of expression levels with clinicopathological features was generated through cBioPortal. We conducted the functional enrichment analysis with Metascape. Results: The expression of ANGPTL1/3/6 was lower in GC tissues than in normal gastric tissues. High expression of ANGPTL1/2/4 was correlated with short overall survival and post‐progression survival in GC patients. Upregulated ANGPTL1/2 was correlated with higher histological grade, non‐intestinal Lauren classification, and advanced T stage, while ANGPTL4 exhibited high expression in early T stage, M1 stage, and non‐intestinal Lauren classification. Conclusions: Integrative bioinformatics analysis suggests that ANGPTL1/2/4 may be potential therapeutic targets in GC patients. Among them, ANGPTL2 acts as a GC promoter, while ANGPTL1/4's role in GC is still uncertain. Abstract : Integrative bioinformatics analysis suggests that ANGPTL1/2/4 may be potential therapeutic targets in GC patients. Among them, ANGPTL2 acts as a GC promotor, while ANGPTL1/4's role in GC is still uncertain.